Performance of One-way Composite Reinforced Concrete Slabs under Explosive-induced Blast Loading. Issue 1 (December 2020) - Anas, S M; Alam, M; Umair, M
Abstract: A finite element model is developed in ABAQUS/CAE to simulate the behavior of one-way reinforced concrete slabs under air-blast loading. Several published empirical equations have been utilized to model air-blast pressure, P(t), for different combinations of the explosive charges and standoff distances. The values of the peak overpressure have been taken from the field explosion tests conducted on four normal reinforced concrete (NRC) slabs of size 2000 mm x 1000 mm x 100 mm in the School of Civil, Environmental, and Mining Engineering, The University of Adelaide, Australia (2009). The slabs were doubly reinforced with HYSD steel re-bars of diameter 12 mm spaced at 100 mm c/c in the major bending plane (ρ = 1.34%) and 200 mm c/c in the other plane (ρ = 0.74%), where "c/c" is the center-to-center distance between two adjacent re-bars. A plasticity-based damage model for concrete and an explicit solver in ABAQUS/CAE are adopted in the finite element (FE) simulation. The available test results and finite element analysis predictions, including maximum mid-span displacement and damage to the RC slabs, are presented and weighed. The computed results are found in good agreement with the experimental ones. The validated model is used to examine the performance of RC slabs with 25% replacement of the conventional steel re-bars by the FRP re-bars of equivalent strength on the compression face only, remote face only, and both faces of the slab. The replacement has been done for higher strength and ductility. Substituted FRP re-bars are of (1) Aramid fiber-reinforced polymer (AFRP), (2) Basalt fiber-reinforced polymer (BFRP), (3) Carbon fiber-reinforced polymer (CFRP), and (4) Glass fiber-reinforced polymer (GFRP). The results are also compared with those obtained with a 50% replacement of the steel re-bars by the FRP re-bars.